Tomato LysM Receptor-Like Kinase SlLYK12 Is Involved in Arbuscular Mycorrhizal Symbiosis - Liao, Dehua; Sun, Xun; Wang, Ning; Song, Fengming; Liang, Yan (Frontiers in Plant Science, 2018)
Arbuscular mycorrhiza (AM) is a widespread symbiotic relationship between plants and fungi (Glomeromycota), which improves the supply of water and nutrients to host plants. AM symbiosis is set in motion by fungal lipochitooligosaccharides, which are perceived by plant-specific LysM-type receptor kinases (LYK). In rice this involves OsCERK1, a LYK also essential for chitin triggered innate immunity. In contrast in legumes, the CERK1 homologous gene experienced duplication events resulting in subfunctionalization. However, it remains unknown whether this subfunctionalization is legume-specific, or has occurred also in other dicot plant species. We identified four CERK1 homologs in tomato (SlLYK1, SlLYK11, SlLYK12 and SlLYK13) and investigated their roles in chitin signaling and AM symbiosis. We found that knockdown of SlLYK12 in tomato significantly reduced AM colonization, whereas chitin-induced responses were unaffected. In contrast, knockdown of SlLYK1 resulted in reduced responses to chitin, but did not alter responses to AM fungi. Moreover, ectopic overexpression of SlLYK1 and SlLYK13 in Nicotiana benthamiana induced cell death, whereas SlLYK12 overexpression did not. Based on our results and comparison with rice OsCERK1, we hypothesize that OsCERK1 orthologs in tomato underwent gene duplication, leading to the subfunctionalization of immunity and symbiosis.